The effects of individual locomotor activity difference on the nicotine sensitization in mice - Kayır, Hakan; Çelik, Turgay (Journal of Dependence, 2003)
Objective: In this study the effects of individual differences in the locomotor activity (LMA) of mice on the development of nicotine-induced sensitization developed by repeated nicotine treatment was investigated.Method: At the beginning of the study, female Swiss –Webster mice were treated with saline for 4 days, daily. They placed into the LMA cages and their LMAs recorded for 30 min immediately after treatment. Mice were separated into groups with low LMA or high LMA, according to their activity scores on the 4th day. After habituation process, separated animals were treated with nicotine (0.5, 1 and 2 mg/kg, ip.) or saline, every second day for 19 days, to produce sensitization. The same procedure was also applied to the non-separated groups of mice.Results: The development of locomotor sensitization was tested separately in mice with low LMA and high LMA, and non-separated mice. High nicotine dose (2 mg/kg) was produced locomotor sensitization in all groups (low LMA, high LMA and non-separated groups). Low dose of nicotine (1 mg/kg) produced locomotor sensitization only in groups with low LMA.Conclusion: Individual LMA differences in mice may be an important factor in the development of nicotine-induced locomotor sensitization. Nicotine-induced sensitization or dependence can be developed easier in mice with low LMA than mice with high LMA.
Keywords: Nicotine; sensitization; locomotor activity; mice